Physicochemical Characterization of Febuxostat Microcomplexes with Parent and Modified Cyclodextrins - Aher, Sayee V; Pore, Yogesh V (Dhaka University Journal of Pharmaceutical Sciences, 2018)
Febuxostat, a BCS class II antigout drug was complexed with β-cyclodextrin (βCD), hydroxypropyl-β- cyclodextrin (HPβCD) and / or methyl-β-cyclodextrin (MβCD), to improve its physicochemical properties. Earlier phase solubility and thermodynamic investigations in acetate buffer (pH 4.5) illustrated AL (linear) type of solubility curve and enthalpy driven complexation process, respectively. The association constant and complexation efficiency of modified cyclodextrins (CDs) were significantly higher than that of parent cyclodextrin (CD). The microcomplexes prepared by spray drying process were examined for their spectral, diffractometric, thermal, particle size, saturation solubility, Log P and dissolution properties. The physicochemical properties of pure drug were improved upon complexation with CDs. However, modified CDs produced amorphous micro-complexes contributing for their better performance as compared to parent CD. Dhaka Univ. J. Pharm. Sci. 17(1): 51-63, 2018 (June)